PDL1 Gene Gain Predicts an Unfavorable Prognosis in HIV-Positive Primary Central Nervous System Lymphoma - Jiamin Chen; Xiaoman Kang; Xinghuan Ding; Yuyang Dai; Lei Sun; Man Li; Ting Liu; Enshan Feng; Xingang Zhou (Current Oncology)
Primary central nervous system lymphoma (PCNSL) refers to non-Hodgkin lymphoma (NHL) originating in the brain, eyes, spinal cord, and cerebrospinal fluid without the presence of lymphoma outside of the central nervous system [...]